Gasification of Biomass in a Fixed Bed Reactor (2014)
Currently, there are different kinds of alternative fuels called "clean fuels" within which hydrogen gas is considered. The hydrogen can be produced by various methods. The aim of this research is producing hydrogen gas by gasification of biomass in a fixed bed reactor, using a gaseous mixture with a high energy potential.